The Mechanism of Establishing Compensation in Land Procurement of the Construction of the Kulon Progo Yogyakarta Solo Toll Road in Klaten District - MG. Thesa Deta Murbasari; Lego Karjoko (IJRAEL: International Journal of Religion Education and Law, 2022)
This journal examines how compensation is determined for land acquisition for toll road construction in Klaten Regency. Instead, the amount of compensation must be decided through deliberations between the land acquisition committee and the party entitled to it. Because they are considered not to care about justice, there are still many people who do not agree with the amount of compensation given. Based on Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest and the Indonesian Appraisal Standard, the price of land for public use is determined by the appraisal team by taking into account physical and non-physical values. This study uses empirical research methods with a focus on descriptive research. Research finding is that there are still many people who do not agree with the amount of compensation given and provide justification to the local District Court, resulting in delays in payment of compensation.